Radio Frequency/Free Space Optical and Radio Frequency-only Wireless Sensor Networks: A Comparative Study of Performance - Sivathasan, S; O'Brien, D (2010)
Wireless sensor networks (WSNs) consist of networked sensor nodes, deployed to sense a phenomenon and report it to a base station. Sensor nodes are small and usually equipped with small batteries with limited capacity, and therefore, one of the most important design considerations for WSNs is power consumption. WSNs expend energy for communications, data processing and sensing; for commonly used RF communications this task accounts for the largest portion of power expended. Hybrid radio frequency/free space optical (RF/FSO) communications has been proposed to reduce power consumption by the sensor node, and in this paper, the performance of the RF/FSO WSN is compared against an RF-only WSN in terms of network lifetime and coverage. Results show that for the wide range of scenarios considered, the RF/FSO WSN lasts at least twice as long as its RF-only counterpart, despite providing the same level of network coverage. This paper also investigates network parameter selection for optimum RF/FSO network coverage. © 2010 by the IETE.